Immunological Quantitation of Rabbit Plasminogen Activator Inhibitor-1 in Biological Samples - Ngo, Thu-Hoa; Declerck, Paul J. (Thrombosis and Haemostasis, 1999)
Two immunoassays for the specific quantitation of rabbit plasminogen activator inhibitor-1 (PAI-1) antigen and activity in biological samples were developed and applied for the evaluation of PAI-1 in rabbits. Levels of PAI-1 antigen in rabbit plasma were 9.8 ± 4.6 ng/ml (mean ± SD, n = 6), with a corresponding value of 20.5 ± 13.5 ng/ml for PAI-1 activity. In rabbit serum PAI-1 antigen was 11.8 ± 4.9 ng/ml (n = 6) and PAI-1 activity was 2.9 ± 2.0 ng/ml (n = 6). Endotoxin injection (20 μg/kg, iv) induced a time-dependent increase of both PAI-1 antigen and PAI-1 activity levels in rabbit plasma, eventually resulting in a 40- to 90-fold increase (p <0.0001 vs baseline). A linear correlation was found between PAI-1 antigen and activity levels in normal plasma (r = 0.90, n = 6, p <0.05) and in plasma from endotoxin-treated rabbits (r = 0.98, n = 20, p <0.001). Analysis of PAI-1 antigen and activity in lysates of washed rabbit platelets revealed the absence of PAI-1 (i.e. <0.03 ng/108 platelets).In conclusion, development of specific immunological assays allowed the quantitation of PAI-1 in rabbit samples. In striking contrast to other species (human, rat, mouse, pig) rabbit platelets lack detectable amounts of PAI-1 (i.e. >100-1000 fold lower vs other species studied). This observation may have important implications for the use of experimental rabbit models especially in studies on the role of platelets in various pathological conditions including thrombosis and atherosclerosis.
Keywords: Thrombosis; fibrinolysis; serpin; atherosclerosis; platelets